Gastric outlet obstruction as a sequel of hydrochloric acid ingestion - Ahsan, S. M. Abu; Ahsan, Tazin (Bangabandhu Sheikh Mujib Medical University Journal, 2017)
Corrosive injury of the upper gastro-intestinal tract is a common cause of morbidity and may result in mortality. Gastric outlet obstruction is a common late sequel, which is best confirmed by esophagogastroduodenoscopy. The surgical management for gastric outlet obstruction has been proven to be beneficial in relieving the symptoms and improving the quality of life. We present here a case of gastric outlet obstruction following hydrochloric acid ingestion as an attempt of self-harm and its surgical management. After the desired surgical treatment, the patient improved clinically which was also reflected in the biochemical results. Proper patient evaluation and planning of operation are vital before surgery.